Comparison Between Size and Stage of Preoperative Tumor Defined by Preoperative Magnetic Resonance Imaging and Postoperative Specimens After Radical Resection of Esophageal Cancer. (24th September 2019) - Gao, Zhenzhen; Hua, Beibei; Ge, Xiaolin; Liu, Jinyuan; Xue, Lei; Zhen, Fuxi; Luo, Jinhua
Background: Our objective is to explore the accuracy of magnetic resonance imaging in determining the preoperative T and N staging, pathological stage, and the length of esophageal tumor in patients with esophageal cancer. Methods: This retrospective analysis included 57 patients admitted to the Department of Thoracic Surgery of The First Affiliated Hospital of Nanjing Medical University between January 2015 and December 2016. Postoperative pathological results were used as the reference to verify the accuracy of magnetic resonance imaging in evaluating tumor T and N staging, pathological stage, and tumor length. The correlation between tumor lengths—measured using magnetic resonance imaging and the surgical specimen measurements—was evaluated. Results: The mean age of the patients was 64.6 ± 7.2 years, with a range of 47 to 77 years. The overall accuracy rate of magnetic resonance imaging in T staging of esophageal cancer was 63.2%; magnetic resonance imaging was generally consistent in the N staging of esophageal cancer. Magnetic resonance imaging and surgical evaluation of tumor length were in excellent agreement (κ = .82, P < .001), while that of gastroscopy and postoperative pathology was moderate (κ = .63, P < .001). Conclusion: Magnetic resonance imaging is highly accurate in determining the preoperative T and N staging, pathologic stage, and tumor length in patients with esophageal cancer, which is important in deciding the choice of preoperative treatment and the surgical approach.